2010
DOI: 10.5114/aoms.2010.14460
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E reversed nicotine-induced toxic effects on bone biochemical markers in male rats

Abstract: IntroductionVitamin E is beneficial in restoring bone histomorphometric parameters in nicotine-treated rats. This study determined the effectiveness of 3 forms of vitamin E in restoring bone metabolism in nicotine-treated rats.Material and methodsThirty-five male Sprague-Dawley rats were divided into 5 groups: (1) control (C), (2) nicotine cessation (NC), (3) α-tocopherol (ATF), (4) tocotrienol-enhanced fraction (TEF) and (5) γ-tocotrienol (GTT). Treatment was carried out for 4 months. The control group was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
6
48
0
1
Order By: Relevance
“…Evidence shows that vitamin E can reverse nicotineinduced toxic effects on bone biochemical markers and osteogenic gene expression [5,6]. These findings were in line with our results, which showed that the negative effects of 5 mM nicotine on ALP/BSP/OC expression significantly decreased in the presence of 5 mM vitamin E to the normal level.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Evidence shows that vitamin E can reverse nicotineinduced toxic effects on bone biochemical markers and osteogenic gene expression [5,6]. These findings were in line with our results, which showed that the negative effects of 5 mM nicotine on ALP/BSP/OC expression significantly decreased in the presence of 5 mM vitamin E to the normal level.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, animal experiments showed that oxidative stress induced by nicotine affected bone metabolism by down-regulating the expression of osteogenic genes [14]. Vitamin E possesses antioxidant properties, and it was shown that it up-regulated osteogenic gene expression in nicotine-treated rats [6] and improved structural, dynamic and cellular histomorphometric parameters of bone [4,5,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies have found that individuals with lower intakes of dietary vitamin E intake had increased risk of hip fracture [4,5], and osteoporotic, postmenopausal women had lower plasma levels of vitamin E [6,7]. Animal models of nicotine exposure, when given α-tocopherol, had increased bone formation, reversal of bone loss [8] and decreased circulating concentrations of inflammatory cytokines [9]. Dose may be critical, as high concentrations of α-tocopherol in cell media did not support viability of osteoblasts [10] and have been shown to be pro-oxidants [11].…”
Section: Introductionmentioning
confidence: 96%